2021
DOI: 10.1016/j.bioactmat.2020.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Combination of magnesium ions and vitamin C alleviates synovitis and osteophyte formation in osteoarthritis of mice

Abstract: Introduction We previously demonstrated that magnesium ions (Mg 2+ ) was a novel therapeutic alternative for osteoarthritis (OA) through promoting the hypoxia inducible factor-1α (HIF-1α)-mediated cartilage matrix synthesis. However, oxidative stress can inhibit the expression of HIF-1α, amplify the inflammation that potentially impairs the therapeutic efficacy of Mg 2+ in OA. Vitamin (VC), a potent antioxidant, may enhance the efficacy of Mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 69 publications
0
29
0
Order By: Relevance
“…Herein, we demonstrated that BTNPs could enhance the therapeutic effect of POP and achieve the same therapeutic effect with just 1/5 dosage of alendronate. As previously reported, a combination of anti-OP drugs and antioxidants, such as Vitamin C/magnesium, magnesium/bisphosphonates, improves the drug's therapeutic effect [ [48] , [49] , [50] ]. In our work, we chemically coupled IONPs with alendronate and prepared novel nanoparticles, which is convenient for drug management compared to separately injection.…”
Section: Discussionmentioning
confidence: 92%
“…Herein, we demonstrated that BTNPs could enhance the therapeutic effect of POP and achieve the same therapeutic effect with just 1/5 dosage of alendronate. As previously reported, a combination of anti-OP drugs and antioxidants, such as Vitamin C/magnesium, magnesium/bisphosphonates, improves the drug's therapeutic effect [ [48] , [49] , [50] ]. In our work, we chemically coupled IONPs with alendronate and prepared novel nanoparticles, which is convenient for drug management compared to separately injection.…”
Section: Discussionmentioning
confidence: 92%
“…More randomized controlled trials or prospective studies are needed to demonstrate that different resorbable materials are better or comparable to titanium screws [ 67 , 68 ]. With regard to the future development of the use of magnesium alloys, further research is needed to increase biocompatibility [ 69 ], to control the corrosion rate [ 70 ], and to reduce gaseous hydrogen production [ 71 ]. It should be possible to compare magnesium-based materials based on the results of various studies by developing a set of standardized protocols to assess corrosion, biocompatibility, and bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers quantified this data by looking at osteophyte formation and the amount of inflammatory markers found in the synovium. 47 The efficacy of vitamin C intra-articular injections in reducing inflammatory markers was further demonstrated in a 2017 study. 46 Chiu et al outlined multiple inflammatory pathways upon which vitamin C conveys its effect in their two-part study.…”
Section: Animal Studiesmentioning
confidence: 96%